Exploring Patient-Centered Care Through Process Improvement: A Systematic Review of Satisfaction Outcomes - Balharith , Reem Saeed; Alyami , Mona Saeed; Alhassan , Hassan Saleh Omar; ALasloom, Fayez Mohammed Ali; Alsharief , Nasser Mohammed; ALMansour , Abdullah Nasser Monaser; alshahi, Raied saeed; Alqirad, Ali Mohammed Hamad; Alqshanin , Bader Saeed; Al doshan, Hussain Mohammed Hussain Al zaber (Journal of Ecohumanism, 2024)
Patient-centered care (PCC) is a vital approach in modern healthcare, focusing on the individual needs, preferences, and values of patients to enhance their overall experience and satisfaction. Process improvement methodologies, such as Lean, Six Sigma, and workflow optimization, aim to streamline healthcare delivery, reduce inefficiencies, and improve quality of care. This systematic review examines the impact of process improvement interventions on patient satisfaction within PCC frameworks. Database searches of PubMed, Scopus, Web of Science, and CINAHL were conducted, targeting peer-reviewed articles from 2016 to 2024 that measured patient satisfaction outcomes related to process improvements. Thirty-five studies met the inclusion criteria, encompassing various healthcare settings and patient populations. Findings indicate that process improvements, particularly Lean and Six Sigma, positively impact patient satisfaction by reducing wait times, minimizing errors, and improving communication and patient flow. Workflow optimization, although showing slightly varied results, also contributed positively when tailored to specific settings. This review highlights the importance of sustainable, patient-centered process improvement practices and suggests further research to assess long-term impacts and explore innovative tools. The study concludes that integrating process improvement methodologies within PCC frameworks can effectively enhance patient satisfaction and overall healthcare quality.Patient-centered care